PENGARUH LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN, REPUTASI KANTOR AKUNTAN PUBLIK DAN LIKUIDITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Holid, Errina Rismayani (JURNAL RISET AKUNTANSI TIRTAYASA, 2023)
This study aims to examine the relationship between the following variables—leverage, profitability, firm size, reputation of a public accounting firm, liquidity—and the timeliness of financial report submission in trading, service, and investment businesses listed on the Indonesian Stock Exchange in 2020 and 2022. This research is quantitative in nature and makes use of secondary data collected from the Indonesian Stock Exchange. The method of purposive sampling was used to choose 93 different businesses. As an analytical method, logistics regression analysis makes use of the SPSSv25 application. Firm size, profitability, liquidity, public accounting firm repute, and leverage were determined to have an impact on the timeliness of financial report submissions in this research. Surprisingly, the issue of timely filing of financial reports was unaffected by any of these criteria.